SUSTAINABLE DEVELOPMENT OF THE AGRO-INDUSTRIAL COMPLEX AND RURAL TERRITORIES OF THE REGIONS - Mukhamed M. Shakhmurzov; Anatoliy S. Gordeev; Valery V. Kulintsev; Yusupzhan A. Yuldashbaev; Nina V. Konik; Radina A. Ulimbasheva; Murat B. Ulimbashev (Юг России: экология, развитие, 2018)
The aim of the study is to monitor the social, performance and financial-economic indicators of each rural area of the region on the basis of an analysis of the "problem map" and the "development reserve diagram", as well as to develop long-term programs for social and economic development. Methods. A package of methodological materials was developed to ensure systematic and comprehensive monitoring of the current state of the rural areas in the region and their reserves of socio-economic development. Results. The authors propose a new methodology for monitoring the sustainable development of the agro-industrial complex and rural areas on the basis of an integrated approach aimed to assess the socio-demographic situation, indicators of agricultural performance, financial and economic parameters and municipal management, which distinguishes it from the well-known methods of analyzing statistical data, municipal reports and economic subjects, expert evaluation of indicators and qualimetric method. The complex nature of monitoring, the objectivity of assessments of social as well as the performance and financial-economic indicators allow us to figure out the rating of each rural area of the region, which should be taken into account when providing government support and subsidizing agriculture and supporting the rural areas. Conclusion. We suggest, developed by us, a scheme of the guaranteed strategic development of rural areas which can be implemented in any region of Russia subject to the creation of maps of land zoning, development of regional and municipal schemes for the rational allocations, production and processing of agricultural products, development of a package of regulatory and legal documents, practical tools and recommendations, regulatory and legal framework for improving leases, development of a methodology to monitor the current state of the rural areas and their reserves of socio-economic the development.